Comparisons of Different PWM Methods with Level-Shifted Carrier Techniques for Three-Phase Three-Level T-Type Inverter - Bıçak, Aykut; Gelen, A. (Institute of Electrical and Electronics Engineers Inc., 2020)
In this paper, total harmonic distortions (THD) and DC bus utilization of three-level T-type inverter (3LT2I) are measured and classified according to the different pulse width modulation (PWM) methods. The analyses have been done for the specific values of the modulation index in the different modulation and carrier signal. Carrier signal techniques are separated to such as being phase disposition (PD) and phase opposition disposition (POD) in multi-level inverters. Performance of the proposed trapezoidal PWM (TPWM) methods that analyzed has compared the various PWM methods regarding DC bus utilization and Total Harmonic Distortion for different values of modulation index. © 2020 IEEE.
7th International Conference on Electrical and Electronics Engineering, ICEEE 2020 -- 14 April 2020 through 16 April 2020 -- -- 160450
Keywords: Phase disposition; Phase opposition disposition; Three level T-type inverter; Total harmonic distortion (THD); Trapezoidal PWM